Pemanfaatan Media Sosial Bagi Ibu Ibu Rumah Tangga dan Pemuda di Desa Arjasari Kecamatan Arjasari Kabupaten Bandung - Soecipto Soecipto; Abdul Holik (LPPM UNINUS, 2018)
Social media is a communication tool that is able to penetrate public and private spaces freely. There is almost no space that is not touched by social media. On the one hand social media is able to connect fraternity, but on the other hand it can damage a family relationship. Here the need for social media literacy that using of social media does not break relationships. Social media is not to damage but to build relationships that have not been established and strengthen relationships that have been established. Social media is a tool to strengthen relationships. Furthermore, social media must be able to improve the welfare of the community through online businesses that are currently developing.